Pathology of Clostridial Enterotoxaemia associated with Pulpy Kidneys in Hamari Lambs in Khartoum: Case Report - Elfadl, Ahmed K.; Elmgboul, Walieldin E.; Mageed, Mahmoud; Ahmed, Amjad S. (Journal of Veterinary Medicine and Animal Production, 2022)
To the best knowledge of the author, this report describes for the first time the pathology of enterotoxaemia occurred due to clostridium perfringens in Sudanese Sheep. Three animals out of 20 fattening Hamari (desert eco-type) lambs showed diarrhea and weakness. Two lambs died and subsequently submitted for necropsy. Diagnosis was confirmed by presence of the typical short bacilli with round ends bacteria in mucosa of spiral colon. Both lambs showed signs of toxemia, where petechiae were noticed in endocardium, pericardium, mucosa of spiral colon and duodenum. Considering the time from death till necropsy, kidneys in both animals were remarkably soft and fragile (pulpy) which is a sign of rapid autolysis due to clostridial toxins. Encephalomalacia and remarkable infiltration of oligodendroglia were evident in 1 lamb, while cerebral edema was prominent in the other lamb. In conclusion, diagnosis was established relying on symptoms and lesions; Hemorrhagic inflammation of the duodenum and spiral colon, pulpy kidneys, encephalomalacia and presence of rod-shaped bacilli with round ends clostridium perfringens in colon.